Production of basalt/wood fiber reinforced polylactic acid hybrid biocomposites and investigation of performance features including insulation properties - Aykanat, Onur; Ermeydan, Mahmut Ali (Wiley, 2022)
Environmental concerns of disposals of automotive, building, or packaging applications enforce researchers to find alternative green materials. Hybrid biocomposites, which consists of both natural/man-made fibers and biopolymers, can be an alternative to glass fiber-supported composites. On the other hand, heat and sound insulation are key properties for automotive and building industries and there is limited knowledge about insulation properties of biocomposites. In this study, we produced basalt/beech wood fiber reinforced polylactic acid (PLA) biocomposites by twin-screw extruder, followed by compression molding. We investigated sound and heat insulation properties as well as mechanical and physical properties. Thermogravimetric analysis, Fourier transform infrared and scanning electron microscopy analyses were carried out for thermal, chemical, and morphological characterization of biocomposites, respectively. Analysis revealed that basalt/wood fiber support improved heat and sound insulation of biocomposites; however, water absorption properties reduced by natural fiber loading. Besides, both tensile and flexural strength of the biocomposites reduced by increasing natural fiber loading.
Keywords: acoustic emission and mechanical properties; biocomposites; extrusion; thermal analysis